2019
DOI: 10.1111/dmcn.14360
|View full text |Cite
|
Sign up to set email alerts
|

Communication in children born very preterm: a prospective cohort study

Abstract: Aim To compare language, speech, and voice of children born preterm and at term, and determine relevant predictors of outcome. Method Three hundred infants (150 males, 150 females; 149 born at <30wks’ gestation, 151 term‐born) were prospectively recruited at birth from the Royal Women's Hospital. We administered the Preschool Language Scales, Fifth Edition, Diagnostic Evaluation of Articulation and Phonology, Grade Roughness Breathiness Asthenia Strain Scale, and Pediatric Voice Handicap Index at 3 years, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…This study compared the performance of the neurotypical control group reported in Sanchez et al (2020) with normative data for children of the same age (see Appendix 1), particularly the DEAP's normative data as both samples used the same materials, procedure and scoring. Sanchez et al (2020) reported data collected in 2015 from 99 three-year-olds (48% girls) recruited as newborn infants at hospitals in Melbourne from late 2011 to early 2013. They were a neurotypical control group for a study investigating speech and language outcomes.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study compared the performance of the neurotypical control group reported in Sanchez et al (2020) with normative data for children of the same age (see Appendix 1), particularly the DEAP's normative data as both samples used the same materials, procedure and scoring. Sanchez et al (2020) reported data collected in 2015 from 99 three-year-olds (48% girls) recruited as newborn infants at hospitals in Melbourne from late 2011 to early 2013. They were a neurotypical control group for a study investigating speech and language outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…The literature reviewed led to the following research question: Do assessment data collected in 2015 (reported in Sanchez et al, 2020) from three-year-old neurotypical children using the DEAP (Dodd et al, 2002) reflect widely accepted normative data for consonant acquisition and phonological patterns? It was hypothesised that there would be no differences in speech development norms over time.…”
Section: Research Question and Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Zimmerman, Steiner, & Pond, 2011) and approximately 20 min of unstructured play with one of five trained pediatric speech-language pathologists. The primary outcomes from the PLS-5 assessment for the entire cohort are reported in a separate paper (Sanchez et al, 2019). Parents were also asked whether their child had received a diagnosis of a neurodevelopmental disorder, such as autism spectrum disorder or cerebral palsy, and whether their child understood or spoke more than one language.…”
Section: Three-year Data Collectionmentioning
confidence: 99%